2009
DOI: 10.1063/1.3089287
|View full text |Cite
|
Sign up to set email alerts
|

Permanent-magnet helicon sources and arrays: A new type of rf plasma

Abstract: Helicon discharges are known for their ability to produce high densities of partially ionized plasma, their efficiency arising from an unusual mechanism of RF coupling. However, the requirement of a dc magnetic field has prevented their wide acceptance in industry. The use of permanent magnets greatly simplifies helicon sources, and arrays of small sources extends the use of helicons to the processing of large substrates. An eight-tube array was designed and constructed, and its density uniformity measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…A number of other researchers have noted a correlation between the wave phase velocities and certain significant electron velocities 5,6,10 ͑such as the velocity of electrons giving a peak in the ionization rate͒, which could lead to wave-particle interactions. 10 Low field helicons are particularly attractive for plasma processing 13,14 or space propulsion applications, 15 where the small field needed reduces the required equipment and system hardware, while also having significantly lower power requirements ͑since the power consumption in any solenoids is proportional to B 0 2 ͒ or none at all if permanent magnets are used. While some work has been done on these low field helicons in nonuniform magnetic fields, 7,15 the majority of work has typically focused on uniform fields.…”
Section: Introductionmentioning
confidence: 99%
“…A number of other researchers have noted a correlation between the wave phase velocities and certain significant electron velocities 5,6,10 ͑such as the velocity of electrons giving a peak in the ionization rate͒, which could lead to wave-particle interactions. 10 Low field helicons are particularly attractive for plasma processing 13,14 or space propulsion applications, 15 where the small field needed reduces the required equipment and system hardware, while also having significantly lower power requirements ͑since the power consumption in any solenoids is proportional to B 0 2 ͒ or none at all if permanent magnets are used. While some work has been done on these low field helicons in nonuniform magnetic fields, 7,15 the majority of work has typically focused on uniform fields.…”
Section: Introductionmentioning
confidence: 99%
“…Details on the inductance limit are given in Ref. 3. Note that the quartz tube is flared out into a "skirt" at the bottom.…”
Section: Apparatusmentioning
confidence: 99%
“…This effect causes a useful increase in density occurring at a density that depends on the magnetic field and the length of the discharge tube. An array of eight small tubes, built several years ago 3 , successfully produced plasmas of density in the 10 11 cm -3 range, uniform over 56 cm width. This experiment demonstrated that a simple, inexpensive helicon arrays can cover large substrates with uniform plasma for roll-to-roll processing.…”
Section: Introductionmentioning
confidence: 99%
“…A proof of principle that an array of multiple sources can produce an uniform plasma has already been carried out in Argon 6 . The investigation of Helicon coupling in hydrogen and deuterium discharges is being carried out at a small laboratory setup (see Fig 4).…”
Section: Helicon Dischargementioning
confidence: 99%